2014
DOI: 10.1155/2014/841892
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Arsenic Minerals Mediated by Dissimilatory Arsenate Reducing Bacteria: Estimation of the Physiological Potential for Arsenic Mobilization

Abstract: The aim of this study was characterization of the isolated dissimilatory arsenate reducing bacteria in the context of their potential for arsenic removal from primary arsenic minerals through reductive dissolution. Four strains, Shewanella sp. OM1, Pseudomonas sp. OM2, Aeromonas sp. OM4, and Serratia sp. OM17, capable of anaerobic growth with As (V) reduction, were isolated from microbial mats from an ancient gold mine. All of the isolated strains: (i) produced siderophores that promote dissolution of minerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Compared with the control, IMH slightly enhanced (p < 0.01) total Fe release, possibly because of disaggregation of minerals in the residue induced by IMH colonization and physical penetration into the mineral surface. 27 This speculation was justified by our SEM characterization ( Figure S2 of the SI), which showed that the microbial incubation induced the crushing of As-bearing minerals from a large lamellar assembly (about 20−50 μm, Figure S2a−c of the SI) to small particles (about 100 nm, Figure S2d−f of the SI).…”
Section: Environmental Science and Technologymentioning
confidence: 68%
“…Compared with the control, IMH slightly enhanced (p < 0.01) total Fe release, possibly because of disaggregation of minerals in the residue induced by IMH colonization and physical penetration into the mineral surface. 27 This speculation was justified by our SEM characterization ( Figure S2 of the SI), which showed that the microbial incubation induced the crushing of As-bearing minerals from a large lamellar assembly (about 20−50 μm, Figure S2a−c of the SI) to small particles (about 100 nm, Figure S2d−f of the SI).…”
Section: Environmental Science and Technologymentioning
confidence: 68%
“…solubilization by these strains is most likely not due to release of OA. We hypothesize that these strains do not produce OA in As-contaminated soil in order to avoid As solubilization since OA release may cause arsenopyrite (FeAsS) dissolution, even if little efficient (59).…”
Section: Table 4 4 Discussionmentioning
confidence: 99%
“…The 96-well plates were incubated at 29 °C for 96 h, 120 r.p.m., and later the OD 600 was read in a Multiskan FC Microplate Photometer (Thermo Fischer Scientific). The MIC was the minimal concentration of metal that inhibited the microbial growth [25]. Amylolytic and proteolytic activity, production of siderophores and solubilization of phosphates were tested on the strains according to Estrada-de los Santos et al .…”
Section: Phenotypic Characterizationmentioning
confidence: 99%